Electronic music studio opening - Parra Cancino, Juan; Opening of Electronic Music Studio University of Limerick, Ireland April 8-12, 2024 (2024)
guitar, trumpet, and electronics.
Lecture, workshop, and performance of Three States of Wax (Juan Parra Cancino, guitar + electronics & Jonathan Impett, trumpet + electronics)
FRIS
Editorial review
Keywords: Music, Thought and Technology